Nearly Efficient Likelihood Ratio Tests of the Unit Root Hypothesis - Jansson, Michael; Nielsen, Morten Ørregaard (Econometrica, 2012)
Seemingly absent from the arsenal of currently available "nearly e¢ cient" testing procedures for the unit root hypothesis, i.e. tests whose asymptotic local power functions are virtually indistinguishable from the Gaussian power envelope, is a test admitting a (quasi-)likelihood ratio interpretation.We study the large sample properties of a quasi-likelihood ratio unit root test based on a Gaussian likelihood and show that this test is nearly e¢ cient.